2016
DOI: 10.1515/sab-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Economic Efficiency of Selected Crops Cultivated under Different Technology of Soil Tillage

Abstract: The objective of this study was the model comparison and economic evaluation of different methods of soil tillage and crop stand establishments used. Based on yield results (winter wheat, spring barley, and white mustard cultivated in three-crop rotation) from field experiments with conventional, conservation with minimum tillage, and no-tillage methods conducted at the site Prague-Ruzyně, model economic balances were evaluated. Prices of the main products were determined based on the yield results from the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Besides technical issues, economic, environmental, social, human health risk/toxicological, and policy aspects are the main issues when assessing the cost-effectiveness and sustainability of white mustard cultivation, processing, and utilization. A few studies have investigated the socio-economic implications of white mustard cultivation and processing (Withers et al, 2000;Sharma, 2015;Vach et al, 2016), but only Tabtabaei et al (2015) has reported on white mustard oil-based biodiesel production costs. According to Withers et al (2000), white mustard is a viable alternative crop for crop rotations for at least three reasons: (a) better utilization of existing equipment on farms, (b) increased diversification, and (c) contribution to weed and disease control with fewer chemicals than other crops.…”
Section: Economic Environmental and Social Considerations Of White mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides technical issues, economic, environmental, social, human health risk/toxicological, and policy aspects are the main issues when assessing the cost-effectiveness and sustainability of white mustard cultivation, processing, and utilization. A few studies have investigated the socio-economic implications of white mustard cultivation and processing (Withers et al, 2000;Sharma, 2015;Vach et al, 2016), but only Tabtabaei et al (2015) has reported on white mustard oil-based biodiesel production costs. According to Withers et al (2000), white mustard is a viable alternative crop for crop rotations for at least three reasons: (a) better utilization of existing equipment on farms, (b) increased diversification, and (c) contribution to weed and disease control with fewer chemicals than other crops.…”
Section: Economic Environmental and Social Considerations Of White mentioning
confidence: 99%
“…Mustard cultivation and processing is profitable on every scale, with opportunities to increase yield and profit through the efficient management and adoption of improved seed varieties, fertilizers, and plantprotective chemicals. Vach et al (2016) investigated the economic efficiency of three crops (white mustard, winter wheat, and spring barley) cultivated using conventional, conservation with minimum tillage, and no-tillage methods. No-tillage produced the highest average white mustard seed yield but seed yields in other tillage methods were not significantly lower.…”
Section: Economic Environmental and Social Considerations Of White mentioning
confidence: 99%
“…Meanwhile, as emphasized by Jat et al [22] and Falcone et al [23], the application of various tillage technologies can affect the level of profitability due to the differentiation of crops and costs of production. In the market economy setting, decisions related to the selection of the production structure and tillage method are not made based on yield and quality only but they also take economic results into account [24]. The costs of production are a fundamental factor determining the economic efficiency of production; hence their level should be subject to review, as well as to detailed planning and control [25].…”
mentioning
confidence: 99%
“…Håkansson (2005) outlined that soil-protected tillage can also positively affect soil properties, such as bulk density or porosity, accumulation of soil organic matter, and less mobile nutrients in topsoil layer. The economic evaluation of CT, NT, and MT for silage maize was based on our previous experiences from evaluation of winter wheat, spring barley and white mustard (Vach et al 2016), on "Normatives of agricultural production technologies" (Kavka et al 2006) and the normatives of the cropping technologies (www. agronormativy.cz).…”
Section: Evaluation Of Soil Tillage Methods On Maize Yield and Financmentioning
confidence: 99%